Perancangan Bangku Doa Jemaat Pada Gereja Katolik Santo Yohanes Evangelista Kudus Dengan Pendekatan Ergonomi - Sokhibi, Akh.; Christata, Bellachintya Reira; Wibowo, Budi Cahyo (Jurnal Rekayasa Sistem Industri, 2025)
The church is a place of worship for Christians. Its presence is expected to provide both physical and spiritual tranquility. To achieve this, church facilities must strive to offer comfort to their users, such as the congregation's prayer benches. However, some of these prayer benches fail to provide sufficient comfort because, historically, church bench designs are relics from the past, dating back to when the church was first established, and did not take comfort into account during their design. This is also the case at the Catholic Church of St. John the Evangelist in Kudus, where the congregation's prayer benches are still the original design from when the church was founded. As a result, there have been several complaints about the discomfort from users. The method used in this study employs an ergonomic approach to redesign the congregation's prayer benches at the Catholic Church of St. John the Evangelist in Kudus. Anthropometric data used to design the prayer benches were gathered from Javanese and Chinese ethnic groups, both male and female. The results of the study yielded a design for the prayer benches at the Catholic Church of St. John the Evangelist in Kudus, with the following dimensions: prayer bench length = 334.96 cm; bench width = 43.80 cm; bench height = 39.2 cm; shoulder rest height = 47.53 cm; and prayer handrest height = 60.17 cm. Another outcome of this study is the implication for the church congregation, which is an increased perception of comfort in the design of the prayer benches through the ergonomic approach.